1999
DOI: 10.2166/wst.1999.0335
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Assessment of the Impact of Draining of Iraqi Marshes on Kuwait's Northern Marine Environment. Part II. Sediment Associated Pollutants

Abstract: Kuwait's northern marine area is considered to be the receiving basin for the influx of sediments and associated pollutants from the Shatt Al-Arb estuary. In recent years, Iraq has undertaken to drain the southern marshes, which acted as a sink for the associated pollutants. This loss of marshes is expected to have far reaching consequences on the ecology of the northern Gulf. Bottom sediments from the area likely to be impacted by the draining of the marshes were studied for a variety of parameters. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 0 publications
0
8
1
Order By: Relevance
“…Particularly high levels of contamination were observed across a number of transects close to Shuaiba Harbour, with total PAH concentrations ranging from 201 to 1333 lg kg À1 dw. Such values are considerably higher than those reported at other locations around Kuwait (Saeed et al, 1999c;de Mora et al, 2010;. Interestingly, this research noted that high molecular weight PAHs dominated the profiles at sites around the SIA, which differs when compared with the dominance of low molecular weight PAHs at sites in and around Kuwait Bay (Al-Omran and Rao, 1997; Lyons et al, this issue-a).…”
Section: Marine Sediment Contaminationmentioning
confidence: 56%
“…Particularly high levels of contamination were observed across a number of transects close to Shuaiba Harbour, with total PAH concentrations ranging from 201 to 1333 lg kg À1 dw. Such values are considerably higher than those reported at other locations around Kuwait (Saeed et al, 1999c;de Mora et al, 2010;. Interestingly, this research noted that high molecular weight PAHs dominated the profiles at sites around the SIA, which differs when compared with the dominance of low molecular weight PAHs at sites in and around Kuwait Bay (Al-Omran and Rao, 1997; Lyons et al, this issue-a).…”
Section: Marine Sediment Contaminationmentioning
confidence: 56%
“…The Iraqi freshwater environment, in general, and the southern marshy habitats in particular suffered from various types of pollution especially that related to pesticides, hydrocarbons or heavy metal toxicants. A higher chemical pollution in the marshes and rivers was previously reported (DouAbul et al, 1988;Saeed et al, 1999). The levels of pollution in marshes have increased substantially in recent years (Al-Imarah et al, 2006).…”
Section: Introductionmentioning
confidence: 77%
“…Moreover, the Mesopotamian Marshes draining into the Shatt Al-Arab that were once acting as a powerful filter for pollutants 14 have tremendously degraded due to the extensive drainage and diversion of water supplies for agriculture, oil exploration, and military purposes in the 1990s 104 www.nature.com/scientificreports www.nature.com/scientificreports/ efforts have been made to restore the marshes since 2003, but restoration is patchy because of high soil and water salinities 105 . Furthermore, upstream dam projects now control the volume and timing of water coming into the marshes, and the total volume of incoming water has diminished [105][106][107] found that the projected water yield reduction that causes lower discharge in the channel could affect both terrestrial and aquatic ecosystems. Thus, these natural purification systems (i.e., Mesopotamian Marshes) are still far from adequate restoration [15][16][17] .…”
Section: Discussionmentioning
confidence: 99%